2017
DOI: 10.1161/atvbaha.117.309580
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Oxidative Stress Promotes Atherosclerosis and Neutrophil Extracellular Traps in Aged Mice

Abstract: Rationale Mitochondrial oxidative stress (mitoOS) has been shown to be increased in various cell types in human atherosclerosis and with aging. However, the role of cell type-specific mitoOS in atherosclerosis in the setting of advanced age and the molecular mechanisms remain to be determined in vivo. Objective The aim of this study was to examine the role of myeloid-cell mitoOS in atherosclerosis in aged mice. Approach and Results Lethally irradiated Ldl receptor-deficient mice (Ldlr−/−) were reconstitute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
76
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(79 citation statements)
references
References 46 publications
(68 reference statements)
2
76
1
Order By: Relevance
“…In vitro experiments show that this metabolic phenotype leads to activation of a pathway involving mitochondrial oxidative stress (mitoOS) and pyruvate kinase M2-mediated STAT3 activation, resulting in increased production of pro-atherogenic IL-6 and IL-1β. Other studies have suggested additional links between mitoOS and human CAD (Paneni et al, 2017), and mitoOS in macrophages increases plaque progression, activates macrophage NF-κB, and promotes the formation of potentially atherogenic neutrophil extracellular traps (NETs) in mouse models of atherosclerosis (Wang et al., 2014; Wang et al, 2017). …”
Section: Energy Metabolism Affects Immune Cell Function In Atherosclementioning
confidence: 99%
“…In vitro experiments show that this metabolic phenotype leads to activation of a pathway involving mitochondrial oxidative stress (mitoOS) and pyruvate kinase M2-mediated STAT3 activation, resulting in increased production of pro-atherogenic IL-6 and IL-1β. Other studies have suggested additional links between mitoOS and human CAD (Paneni et al, 2017), and mitoOS in macrophages increases plaque progression, activates macrophage NF-κB, and promotes the formation of potentially atherogenic neutrophil extracellular traps (NETs) in mouse models of atherosclerosis (Wang et al., 2014; Wang et al, 2017). …”
Section: Energy Metabolism Affects Immune Cell Function In Atherosclementioning
confidence: 99%
“…Recent results of the study conducted by Wang et al (2017) indicated a significant relationship between mitochondrial oxidative stress (mitoOS) and generation of NETs in aged mice with atherosclerosis. Authors of this publication observed that inhibition of mitoOS in aged mice leads to reduction of NET formation, which could not be observed in younger specimens.…”
Section: Introductionmentioning
confidence: 99%
“…57 The perivascular neutrophil microenvironment has been identified as a malleable niche, influenced by the presence of excess O 2 − generated from mitochondria. 58 Likewise, lysophosphatidylcholine has been implicated in mitochondrial ROS production and endothelial cell activation likely due to electron leakage across mitochondrial membranes. 59 Both of these conditions have been implicated in the progression of atherosclerosis through surplus mitochondrial ROS.…”
Section: Reactive Oxygen Speciesmentioning
confidence: 99%